Vegetative and Floral Morphological Studies of Some Species of Hibiscus Linn. in Nigeria - Adedeji, O.; Illoh, H. C. (2014)
A morphological study of ten species of Hibiscus found in Nigeria was conducted in search of useful and stable characters which may enhance the knowledge of the taxonomic status of the genus. Both qualitative and quantitative characters were recorded. Characters of taxonomic value not recorded in the flora of West Tropical Africa include, habit, leaf bases, stipule shape, petal shape, fruit shapes and apices. A new key to the Hibiscus species is included.